2011
DOI: 10.1161/strokeaha.110.603787
|View full text |Cite
|
Sign up to set email alerts
|

Coffee Consumption and Risk of Stroke in Women

Abstract: Background and Purpose-Coffee consumption has been inconsistently associated with stroke incidence and mortality in previous studies. We investigated the association between coffee consumption and stroke incidence in the Swedish Mammography Cohort. Methods-We prospectively followed of 34 670 women without a history of cardiovascular disease or cancer at baseline in 1997. Coffee consumption was assessed in 1997 using a self-administered questionnaire. Incident stroke cases were ascertained from the Swedish Hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 19 publications
4
59
0
5
Order By: Relevance
“…But the threshold daily amount of theobromine to modulate platelet function requires further investigation. Studies of coffee consumption, where caffeine is clearly a key bioactive, have also shown a reduced risk of CHD mortality and ischaemic stroke in habitual coffee drinkers [45][46][47]. When these findings are considered in conjunction with observations from chocolate studies, this suggests that daily intake of methylxanthines is a key dietary factor modulating platelet function.…”
Section: Platelet Aggregationmentioning
confidence: 88%
“…But the threshold daily amount of theobromine to modulate platelet function requires further investigation. Studies of coffee consumption, where caffeine is clearly a key bioactive, have also shown a reduced risk of CHD mortality and ischaemic stroke in habitual coffee drinkers [45][46][47]. When these findings are considered in conjunction with observations from chocolate studies, this suggests that daily intake of methylxanthines is a key dietary factor modulating platelet function.…”
Section: Platelet Aggregationmentioning
confidence: 88%
“…[10,107] Coffee consumption is the principal supply of antioxidants in the western diet; reduce the risk of cardiovascular and other inflammatory diseases in postmenopausal women.…”
Section: Health Benefit Of Coffee Consumption Description Of Action Smentioning
confidence: 99%
“…Recently, in a cohort of Swedish women (coffee >1 cups/day), risk of stroke was reduced in CI, but not in ICH, compared with <1 cup/day. 8 In recent meta-analyses, the association between coffee consumption and the risk of CHD still remains controversial. 29,30 Our study showed no significant association between coffee consumption and CHD.…”
Section: May 2013mentioning
confidence: 99%